Polymorphisms in Promoter Region of the Interferon - Gamma Receptor1 Gene and its Relation with Susceptibility to Brucellosis - Zahra Naseri; Nasrin Bahmani; Mohammad Yosef Alikhani; Seyed Hamid Hashemi; Ghodratollah Roshanaei (Iranian Society of Pathology, 2019)
Background & Objective: Brucellosis is one of the most prevalent bacterial zoonotic diseases which afflicts both humans and animals. Genetic factors play an important role in susceptibility to brucellosis. One of these factors is interferon-gamma (IFN-g), which is vital in the defense mechanism against infectious diseases such as brucellosis. The purpose of this study was to evaluate the relationship between two single nucleotide polymorphisms (SNPs) at positions -611 and -56 within the promoter region of interferon-gamma receptor-1 gene (IFN-g R1) and brucellosis. Methods: In this research,thegenomic DNA was collected from 60 peripheral blood samples infected with brucellosis and 68 healthy volunteers. DNA was extracted by salting out method. Then, DNA genotypes were analyzed using polymerase chain reaction-restriction fragment length polymorphisms (PCR-RFLP). Results: The results showed that there is a significant difference in -611 SNP frequencies between control and patient groups. At position -611, CC genotype was related to patient group (P=0.024) and TT genotype was related to the control group. According to the results, males had a higher frequency of Brucella infection. Conclusion: The presence of C allele in position -611 in IFNγ R1 gene promoter was related to a higher risk of disease and susceptibility to brucellosis. Moreover, the presence of T allele in position -611 in IFN-g R1 gene promoter was related to a lower risk of disease.